Managing Fiscal Risks from National Airlines in Pacific Island Countries - Balasundharam, Vybhavi (IMF Working Papers; Working Paper ;, 2021)
Pacific island countries (PICs) rely on national airlines for connectivity, trade, and tourism. These airlines are being struck hard by COVID-19. Losses will weigh on public sector balance sheets and pose risks to economic recovery. With a backdrop of tight fiscal space and increasing government debt, losses in airlines are adding to fiscal risks in some PICs. This paper discusses tools to evaluate and manage the fiscal risks from national airlines in the Pacific. We present a snapshot of the current state of Public Financial Management (PFM) practices in PICs and detail the best practices. This exercise would illustrate the areas in which PICs have scope to improve their risk management with regard to national airlines. We then discuss the use of diagnostic tools and capacity development to enhance monitoring and risk management. Greater transparency and accountability in the airlines, combined with rigorous oversight, would be the first step towards improved financial management of national airlines.